Czerwony kapturek. (Warszawa : Wydawnictwo Gamma, 1990)
An adaaptation of Little Red Riding Hood for very young children. Ages 3-6.
Pop-up book.
"Ediciones A. Saldaña."
Keywords: Toy and movable books -- Specimens